2020
DOI: 10.1002/acn3.51212
|View full text |Cite
|
Sign up to set email alerts
|

Localization of CDR2L and CDR2 in paraneoplastic cerebellar degeneration

Abstract: Objective: Identify the subcellular location and potential binding partners of two cerebellar degeneration-related proteins, CDR2L and CDR2, associated with anti-Yo-mediated paraneoplastic cerebellar degeneration. Methods: Cancer cells, rat Purkinje neuron cultures, and human cerebellar sections were exposed to cerebrospinal fluid and serum from patients with paraneoplastic cerebellar degeneration with Yo antibodies and with several antibodies against CDR2L and CDR2. We used mass spectrometry-based proteomics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“… 8 , 12 This pattern probably represents ribosomal staining because it has been shown recently that CDR2L interacts with the ribosomal subunit protein rpS6. 10 Sera from 2 of our patients without PCD, but with previous cancer, also stained the rat Purkinje cell cytoplasm, but the cytoplasmic staining was not granular. The specific target for this staining is unknown, but such false positive anti-Yo staining must be interpreted with caution because it is unrelated to PCD.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“… 8 , 12 This pattern probably represents ribosomal staining because it has been shown recently that CDR2L interacts with the ribosomal subunit protein rpS6. 10 Sera from 2 of our patients without PCD, but with previous cancer, also stained the rat Purkinje cell cytoplasm, but the cytoplasmic staining was not granular. The specific target for this staining is unknown, but such false positive anti-Yo staining must be interpreted with caution because it is unrelated to PCD.…”
Section: Discussionmentioning
confidence: 71%
“…[5][6][7] Evidence suggests that anti-Yo targets 2 intracellular antigens, cerebellar degeneration-related protein 2 (CDR2) and CDR2-like (CDR2L), expressed in the nucleus and cytoplasm of Purkinje neurons in the cerebellum, respectively. [8][9][10] The interaction between anti-Yo and CDR proteins is believed to mediate Purkinje neuron dysfunction and death, leaving the patients in a severely disabled state. 11,12 Onconeural antibodies identified in the sera or CSF of patients are key diagnostic biomarkers for PCD.…”
mentioning
confidence: 99%
“…Injured neurons upregulate MHC receptors (4) allowing recognition by cytotoxic T lymphocytes that also contribute to cell death. [Modified from Herdlevaer et al ( 32 )].…”
Section: Pathogenic Mechanisms In Diseases Associated With Antibodies To Neuronal Surface Membrane Antigensmentioning
confidence: 99%
“…It is now recognized that the major Yo antigen may be CDR2L rather than CDR2 and that antibodies directed against CDR2L most closely parallel the antigen-binding seen by human anti-Yo antibodies in cerebellar sections studied using immune electron microscopy as well as by immunohistochemistry and immunoprecipitation ( 28 , 29 , 31 ). It is thus possible that successful production of an animal model for anti-Yo antibody-associated cerebellar degeneration may require immunization with CDR2L rather than CDR2, or, given the possible roles of each antigen in Purkinje cell protein synthesis, that immunization with both proteins might be required ( 32 ). A second issue, involved in passive transfer experiments using human IgG, could be a failure of antibody-mediated pathogenicity to occur across species lines.…”
Section: Pathogenic Mechanisms In Diseases Associated With Antibodies To Intracellular Neuronal Antigensmentioning
confidence: 99%
“…19 To date, there have been mixed findings with regard to intracellular antibodies' direct pathogenic role. 2 In a recent study, Herdlevaer et al 32 reported that anti-Yo antibodies might have a direct effect on disrupting messenger RNA translation and/or protein synthesis. In contrast, other studies reported conflicting results on whether intracellular antibodies, such as anti-Hu antibodies, have a direct role in neuronal injury.…”
Section: Pathogenicity Vs Epiphenomenonmentioning
confidence: 99%